Evaluation of a Human T Cell-Targeted Multi-Epitope Vaccine for Q Fever in Animal Models of Coxiella burnetii Immunity - Sluder, Ann E.; Raju Paul, Susan; Moise, Leonard; Dold, Christina; Richard, Guilhem; Silva-Reyes, Laura; Baeten, Laurie A.; Scholzen, Anja; Reeves, Patrick M.; Pollard, Andrew J.; Garritsen, Anja; Bowen, Richard A.; et al. (Frontiers in Immunology, 2022)
T cell-mediated immunity plays a central role in the control and clearance of intracellular Coxiella burnetii infection, which can cause Q fever. Therefore, we aimed to develop a novel T cell-targeted vaccine that induces pathogen-specific cell-mediated immunity to protect against Q fever in humans while avoiding the reactogenicity of the current inactivated whole cell vaccine. Human HLA class II T cell epitopes from C. burnetii were previously identified and selected by immunoinformatic predictions of HLA binding, conservation in multiple C. burnetii isolates, and low potential for cross-reactivity with the human proteome or microbiome. Epitopes were selected for vaccine inclusion based on long-lived human T cell recall responses to corresponding peptides in individuals that had been naturally exposed to the bacterium during a 2007-2010 Q fever outbreak in the Netherlands. Multiple viral vector-based candidate vaccines were generated that express concatemers of selected epitope sequences arranged to minimize potential junctional neo-epitopes. The vaccine candidates caused no antigen-specific reactogenicity in a sensitized guinea pig model. A subset of the vaccine epitope peptides elicited antigenic recall responses in splenocytes from C57BL/6 mice previously infected with C. burnetii. However, immunogenicity of the vaccine candidates in C57BL/6 mice was dominated by a single epitope and this was insufficient to confer protection against an infection challenge, highlighting the limitations of assessing human-targeted vaccine candidates in murine models. The viral vector-based vaccine candidates induced antigen-specific T cell responses to a broader array of epitopes in cynomolgus macaques, establishing a foundation for future vaccine efficacy studies in this large animal model of C. burnetii infection.